Enzymatic and Inhibition Mechanism of Human Aromatase (CYP19A1) Enzyme. A Computational Perspective from QM/MM and Classical Molecular Dynamics Simulations - Sgrignani, Jacopo; Cavalli, Andrea; Colombo, Giorgio; Magistrato, Alessandra (Mini Reviews in Medicinal Chemistry, 2016)
The enzyme human aromatase (HA), a member of the cytochrome P450 family, catalyses in a highly specific and peculiar manner the conversion of estrogens to androgens. Thus, this enzyme is a relevant target for inhibitor design for the treatment of breast cancer and currently there are several HA inhibitors employed in clinical practice. The HA crystal structure was solved only in 2009 and, since then, several studies have been done to characterize a variety of its structural, dynamical and mechanistic properties. In the last decade, the predictive power and the accuracy of computer simulations techniques, either relying on force field or on “ab initio” description of the system, has enormously increased. This was mainly due to the development of more accurate algorithms, which allow accelerating the time-scale accessible by simulations techniques, and to the increase of computer power. Hence, computer simulations can now accurately paint an atomistic picture to the molecular mechanism of biomolecules providing also an estimate of the kinetic and thermodynamic properties of the enzyme at increasingly quantitative level. In this review, on the basis of selected examples taken from our work, we summarize current active research topics concerning HA enzyme, with a focus on computational studies. In particular, we will illustrate current results and novel hypothesis concerning the final (rate-determining) aromatization step promoted by this enzyme, on how the structural/dynamics/functional properties of HA are modulated in a membrane lipophilic environment, and finally on novel possible (allosteric) inhibition mechanisms which may modulate estrogen production in HA.
Keywords: Enzymatic